The correlation of serum Asprosin with diabetic nephropathy - Abdulsada, Abdulaziz Q; Albadr, Abrar I (Edelweiss Applied Science and Technology, 2025)
Asprosin, a recently identified adipokine, promotes glucose synthesis in the liver. Diabetic nephropathy (DN) is the primary cause of end-stage renal disease. Asprosin has been linked to inflammation and insulin resistance, both critical to DN development. This study aimed to investigate the correlation between serum asprosin levels and DN in patients with type 2 diabetes (T2DM). A total of 180 participants were included in this study: 129 patients with T2DM and 51 healthy controls. Patients were divided into three groups based on their urine albumin to creatinine ratio (UACR): DN0 group (UACR < 30 mg/g), DN1 group (30 ≤ ACR < 300 mg/g), and DN2 group (≥ 300 mg/g). T2DM patients had greater serum asprosin levels than members of the control group. Looking at the various forms of diabetic nephropathy, the DN2 group had notably more asprosin in their blood than the DN0 and DN1 groups. Furthermore, more asprosin was present in the blood of the DN1 group than in the DN0 group. Serum asprosin levels were also strongly correlated with the duration of the disease, blood pressure, increasing blood sugar, glycated hemoglobin, total cholesterol, triglycerides, low-density lipoprotein cholesterol, urea, creatinine, and UACR. Conversely, high-density lipoprotein cholesterol and estimated glomerular filtration rate (eGFR) were negatively correlated very substantially. As DN deteriorated, asprosin levels in the blood increased. Apart from that, asprosin had a negative connection with eGFR and a positive one with UACR.